Forest cover and environment type shape functional diversity of insectivorous birds within the Brazilian Atlantic Forest - Manzoli, Enzo C (2024)
Tropical insectivorous birds comprise a diverse group that has a distinct response to habitat degradation. However, knowledge on birds' ecological functions and their large-scale functional responses to human impacts across various habitats is scarce. We sampled 22 1-km-radius buffer landscapes within the Cantareira-Mantiqueira region (south-east Brazil), including native forests, pastures and marshes, to assess how landscape and habitat characteristics might affect insectivorous birds within the Brazilian Atlantic Forest. We studied whether bird species and functional diversity might respond to habitat turnover and nestedness and to native forest cover using generalized linear mixed models. We found negative effects of increased native forest cover on functional diversity indices. Bird communities in pastures show more nestedness, whereas marsh areas exhibit higher turnover. Forest areas receive a balanced contribution from both nestedness and turnover. These results are attributable to the predominantly secondary growth and early successional stages of the native forest fragments in the region, emphasizing the connection between landscape characteristics, habitat types and bird functional diversity in the Brazilian Atlantic Forest.